Microwave ablation of porcine kidneys in vivo: effect of two different ablation modes (“temperature control” and “power control”) on procedural outcome - Sommer, Christof-Matthias; Arnegger, Florian; Koch, Vitali; Pap, Bence; Holzschuh, Maria; Bellemann, Nadine; Gehrig, Tobias; Senft, Jonas; Nickel, Felix; Mogler, Carolin; Meinzer, Hans-Peter; Stampfl, Ulrike; et al. (CardioVascular and interventional radiology, 2012)
Purpose: This study was designed to analyze the effect of two different ablation modes (“temperature control” and “power control”) of a microwave system on procedural outcome in porcine kidneys in vivo. Methods: A commercially available microwave system (Avecure Microwave Generator; MedWaves, San Diego, CA) was used. The system offers the possibility to ablate with two different ablation modes: temperature control and power control. Thirty-two microwave ablations were performed in 16 kidneys of 8 pigs. In each animal, one kidney was ablated twice by applying temperature control (ablation duration set point at 60 s, ablation temperature set point at 96°C, automatic power set point; group I). The other kidney was ablated twice by applying power control (ablation duration set point at 60 s, ablation temperature set point at 96°C, ablation power set point at 24 W; group II). Procedural outcome was analyzed: (1) technical success (e.g., system failures, duration of the ablation cycle), and (2) ablation geometry (e.g., long axis diameter, short axis diameter, and circularity). Results: System failures occurred in 0% in group I and 13% in group II. Duration of the ablation cycle was 60 ± 0 s in group I and 102 ± 21 s in group II. Long axis diameter was 20.3 ± 4.6 mm in group I and 19.8 ± 3.5 mm in group II (not significant (NS)). Short axis diameter was 10.3 ± 2 mm in group I and 10.5 ± 2.4 mm in group II (NS). Circularity was 0.5 ± 0.1 in group I and 0.5 ± 0.1 in group II (NS). Conclusions: Microwave ablations performed with temperature control showed fewer system failures and were finished faster. Both ablation modes demonstrated no significant differences with respect to ablation geometry.